Efektivitas Pemberian Terapi Latihan Terhadap Aktivitas Fungsional Pada Pasien Claw Hand E.C. Morbus Hansen: Studi Kasus - Ashabul Jannah Kholiliyah; Taufik Eko Susilo; Teguh Prihastomo (Pusat Riset dan Inovasi Nasional, 2024)
Leprosy is a chronic infectious disease caused by Mycobacterium leprae that affects the skin, peripheral nerves, mucosal surfaces of the respiratory tract, muscles and bones. Most leprosy patients experience paralysis of the ulnar nerve which causes partial disruption of the fingers or called clawhand where the finger is like a bird's claw. Purpose: this study is to determine the benefits of exercise therapy on functional activity in patients with Claw Hand e.c Morbus Hansen. Method: This study uses a case report method conducted at Kelet Donorejo Hospital by taking a sample of one of the leprosy patients by providing exercise therapy for 3 therapy sessions. Furthermore, measuring the first therapy and the third therapy. Results: In this study, the results of physiotherapy interventions were obtained, namely showing an increase in muscle strength even though it was not significant, showing a decrease in pain, in measuring nerve thickening there was no change, motor nerve function and functional measurements of the hand there was an increase even though it was not significant. Conclusion: Physiotherapy management in patients with claw hand e.c. multi-bacillary morbus hansen in the form of active exercise therapy, strengthening exercise and functional exercise obtained the results of increased muscle strength even though it was not significant, showed a decrease in pain, in the measurement of nerve thickening there was no change, motor nerve function and functional hand measurements there was an increase even though it was not significant.